Combined internal fixation and transarticular external skeletal fixation to treat traumatic patellar fractures in five dogs. Issue 2 (4th March 2022) - Sprocatti, M; Kvale, E; Solano, M
ABSTRACT: Case history: Medical records of dogs (n = 5) that had been treated for patellar fracture with transarticular external skeletal fixation (TA-ESF) to augment internal fixation, at a single referral hospital in the United Kingdom between 2015 and 2017, were reviewed. Clinical findings and treatment: At presentation, two dogs had polar patellar fractures, two had comminuted fractures and one dog had a transverse fracture. The median age at the time of the surgery was 21 (min 8, max 132) months and the median body weight was 19.0 (min 8.3, max 28.6) kg. In all cases, TA-ESF (Type IA lateral triangulated or modified Type II) was used in combination with internal fixation with pins and/or orthopaedic wire, supported by nylon leader line (patella-to-tibia mattress suture) and/or absorbable suture in a locking loop and/or circum-patellar pattern. All cases had short-term (6–12 weeks) post-operative radiographic follow-up, which showed evidence of fracture healing in 2/5 cases. All TA-ESF were removed 6 or 7 weeks post-operatively and four dogs had minor complications related to TA-ESF. More than 2 years post-operatively, the owners of all dogs were contacted and questioned using the Liverpool Osteoarthritis in Dogs questionnaire regarding the mobility of their pet. Four of the five cases were re-examined to evaluate their long-term outcomes. Based on the results of goniometric measurement of stifle range of motion, subjective gait assessment and objective gait analysis with a pressure-sensitive walkway, all dogs showed a satisfactory outcome at the final follow-up. Clinical relevance: A combination of internal fixation and TA-ESF for stabilisation of traumatic patellar fractures is a valid treatment option. Further investigations with larger case numbers are necessary to evaluate success and complication rates.